Internal Communication Management among employees toward effective strategic communication - Ilmi, Ahmad Zainal; Farida, Farida; Panuju, Redi; Maella, Nurannafi Farni Syam; Zulaikha, Zulaikha (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
The seamless attainment of strategic objectives and the cultivation of a cohesive and engaged workforce are made possible by effective internal communication, which is essential for the success of a business. This case study investigates the importance of effectively managing internal communication to improve strategic communication within a substantial multinational organization. Current research underscores the significance of internal communication in promoting employee engagement and job satisfaction, fostering the interchange of knowledge, and ensuring that employees are aligned with the organization's objectives. Nevertheless, it is imperative to possess a more profound comprehension of the precise strategies and methodologies that organizations may implement to enhance their internal communication management. This investigation implemented the case study methodology proposed by Robert K. Yin, which entailed the observation of internal communication management procedures, the analysis of documents, and the conduct of in-depth interviews. The aim was to examine the extent to which these practices influence the efficacy of strategic communication within the organization. The research demonstrates that the organization's strategic communication has been improved as a result of its emphasis on internal communication, which has been achieved through the implementation of explicit policies, the utilization of diverse channels, and the involvement of leadership. Employees attain improved alignment with organizational objectives, increased knowledge dissemination, and improved cross-departmental collaboration. The results of the study indicate that in order to optimize communication effectiveness and execute strategic initiatives effectively, organizations should prioritize internal communication. By investing in internal communication management, organizations can cultivate a cohesive, well-informed, and highly engaged workforce, thereby gaining a competitive advantage and achieving long-term success.